Clinical Course and Dietary Patterns Among Patients Incorporating the Autoimmune Protocol for Management of Inflammatory Bowel Disease (P12-010-19). (13th June 2019) - Lee, Joy; Pedretti, Christian; Konijeti, Gauree
Abstract: Objectives: The aim was to examine the clinical course and dietary patterns among patients incorporating autoimmune protocol (AIP) for management of inflammatory bowel disease (IBD). Methods: An anonymous online survey was sent through electronic newsletters and support groups utilizing AIP. The survey assessed demographics, IBD disease activity, and medication use. Participants were asked about AIP utilization and food group reintroductions. Abdominal pain (AP), stool frequency (SF), and rectal bleeding (RB) were compared at baseline (BL, prior to starting AIP), week 6 (after starting AIP), and present, for both Crohn's disease (CD) and ulcerative colitis (UC). Results: There were 78 respondents. Mean age was 39.4 years, with mean IBD duration 13.2 years. 78% had prior steroid exposure. 35% currently on immunosuppressive agents. 73% perceived achieving clinical remission due to AIP. This was more common among patients not on immunosuppression (76% vs. 24% on immunosuppression, P  < 0.001). After starting AIP, 32% reported discontinuing steroids. AIP was initiated according to protocol by 73%, while 27% modified it. Food group reintroductions were started within 0–4 weeks of starting AIP among 8%, while 23% reintroduced within 5–8 weeks, 24% within 2–6 months, 23% within 6–12 months, and 13% after 12 months. Success of food group reintroductions varied (Table 1). Among patients with CD, improvement by ≥1 levels of symptoms by week 6 was reported by 77% for AP, 57% for SF, and 57% for RB. Compared to BL, reported symptoms improved by ≥1 levels in 70% for AP, 53% for SF, and 57% for RB. In contrast, disease worsening by ≥1 levels at week 6 was reported by 7% for AP and none for SF and RB. Among patients with UC, improvement by ≥1 levels by week 6 was reported by 72% for AP, 79% for SF, and 65% for RB. Compared to BL, reported symptoms improved by ≥1 levels in 65% for AP, 67% for SF, and 58% for RB. In contrast, disease worsening by ≥1 levels at week 6 was reported by 2% for AP, 2% for SF, and 5% for RB. Conclusions: Patients utilizing AIP for management of IBD report clinical benefit of AIP, reduction of steroid use, and successful food group reintroduction. Dietary interventions could be another form of treatment in patients with IBD to improve symptoms and maintain remission. Funding Sources: Not applicable. Supporting Tables, Images and/or Graphs: